Studies on the Effect of Flyash and Plant Growth Hormones on Chlorophyll-a,b and Total Chlorophyll Contents in Wheat, Bengal Gram and Sunflower Leaves - Chandra Deshmukh, Naresh; Kumar Sarway, Prakash; Prasad Tyagi, Naresh (Asian Journal of Chemistry, 2016)
In the present work, flyash and plant hormones have been used in the pot experiments in wheat, Bengal gram and sunflower plants to study their effects in chlorophyll contents.